Analysis of Rainfall in the Locality of Babahoyo, for the Programming of Cultivation of Rice (Oryza Sativa L.) - Caicedo-Camposano, Oscar; Mora-Castro, Oscar; Layana-Bajana, Eleonora; Sotomayor-Moran, Arianna; Barbeito-Rodríguez, Rodolfo (European Scientific Journal, ESJ, 2017)
The work was carried out with the objective of knowing the precipitation regime of Babahoyo, Los Ríos in Ecuador and in this way contribute to the improvement of the cropping calendar of “rainfed rice", as this information is commonly required by farmers and agricultural professionals who work as agricultural advisers. A serie of record’s rainfalls were processed in about 35 years belonging to the Babahoyo’s Weather Station of the National Institute of Meteorology and Hydrology situated on the premises of the Faculty of Agricultural Sciences of theTechnical University of Babahoyo (UTB), the methodology applied focuses on the identification of statistics such as the mean, standard deviation, variance, coefficient of variation, asymmetry coefficient and kurtosis coefficient; then on the basis of average is determined dry and wet periods, the frequency and the intensity in which they occur. It was found that in this town from 1980 to 2014 occurred eight dry periods and seven wet periods, that occured with a frequency of 3.4 and 3.7 years respectively. Based on the results, the wet season is defined between the months from December to May and the dry season from June to November. The sheet available average cumulative rainfall, which is determined for wet and dry periods, has the following valuables: 1001,3 mm, 3169 mm and an average of 2167,7 mm. The rainfed rice in the area should be planted from the month of December, to be taken advantage of all the rain of the wet season.